2016
DOI: 10.1039/c6cp00809g
|View full text |Cite
|
Sign up to set email alerts
|

Acyclic forms of aldohexoses and ketohexoses in aqueous and DMSO solutions: conformational features studied using molecular dynamics simulations

Abstract: The molecular properties of aldohexoses and ketohexoses are usually studied in the context of their cyclic, furanose or pyranose structures which is due to the abundance of related tautomeric forms in aqueous solution. We studied the conformational features of a complete series of D-aldohexoses (D-allose, D-altrose, D-glucose, D-mannose, D-gulose, d-idose, D-galactose and D-talose) and D-ketohexoses (D-psicose, D-fructose, D-sorbose and D-tagatose) as well as of L-psicose by using microsecond-timescale molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…The reverse reaction R1 → G was simulated by performing two independent simulations ( R1 → G1 and G1 → G ), as the direct conversion of R1 to G could not be achieved in our simulations. The presence of metastable conformations such as G1 is consistent with previous computational studies . It should be noted that step G1 → G is already part of pathway Cy2 .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The reverse reaction R1 → G was simulated by performing two independent simulations ( R1 → G1 and G1 → G ), as the direct conversion of R1 to G could not be achieved in our simulations. The presence of metastable conformations such as G1 is consistent with previous computational studies . It should be noted that step G1 → G is already part of pathway Cy2 .…”
Section: Resultssupporting
confidence: 90%
“…The presence of metastable conformations such as G1 is consistent with previous computational studies. 135 It should be noted that step G1 → G is already part of pathway Cy2. The reverse reaction F2 → F1b was not simulated here because the relative free energy of F2 is known from the cyclic pathways.…”
Section: ■ Resultsmentioning
confidence: 99%
“…The magnitude of discrepancy observed in the case of the present study is in line with those observed previously for aldohexopyranoses, 15,70 ketohexopyranoses, aldopentofuranoses, and deoxy-and dideoxyaldopentopyranoses 59 as well as for the indirect results concerning acyclic forms of aldo-and ketohexoses. 84 In conclusion, the present force field can be used to study the anomeric equilibrium of furanoses; however, some additional refinements (of character and magnitude dependent on the compound of interest) may be necessary to increase the accuracy of calculations.…”
Section: Journal Of Chemical Theory and Computationmentioning
confidence: 94%
“…† The ATB generated parameters were found to be reliable and have been widely used in several current studies. [48][49][50][51][52][53] However, the effectiveness of ATB parameters was also justied by calculating the transport properties (i.e. self-diffusion coefficient), structural properties (RDF and number of hydrogen bonds) and thermodynamic properties (density) of the TMAO box, and the results were compared with the Shea force eld 54 and the united atom force eld (generated from ATB) of TMAO as a benchmark test; 55 these are reported in the ESI.…”
Section: Methodsmentioning
confidence: 99%